Peningkatan Minat Beli; Peran Komunikasi Bisnis - Rita Erycha; Leonard Adrie Manafe (Universitas Linggabuana PGRI Sukabumi, 2023)
In the world of small, medium and large scale businesses, business people are people who are involved in the business world and they cannot be separated from communication activities. In everyday life communication plays an important role and is a very important basis for socializing, one of which is when organizing in business. The purpose of this study is to analyze the role of business communication carried out by WRP Stores in an effort to increase consumer buying interest. This qualitative research uses data collection techniques in the form of observations that have been made while in the field and also interviews with five random informants with the criteria of having bought products from a WRP store at least once. The results and discussion of research on the role of business communication in an effort to increase consumer buying interest using greetings and customer exploration are very influential. Personal selling in the first impression is very influential also with polite and polite language. The use of language that is easy to understand and able to interact comfortably with customers is also carried out by WRP Store in an effort to increase consumer buying interest.